2016
DOI: 10.1016/j.juro.2016.02.1859
|View full text |Cite
|
Sign up to set email alerts
|

Mp76-08 Serum Levels of Enclomiphene and Zuclomiphene in Hypogonadal Men on Long-Term Clomiphene Citrate Treatment

Abstract: Of 589 men who underwent RP, subjects reported use of at least one erectile aid at 2 years. Frequency of use, and effectiveness of erectile aids, is summarized in Table 1. Factors associated with responsiveness to ED treatment included age, number of comorbidities, baseline PSA, prostate volume, and D'Amico risk stratification. Effectiveness of oral PDE5i was the best predictor of erection quality, defined as erection firm enough for penetration, and sexual satisfaction two years after RP. Of the 140 men in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Because of the different biochemical properties of the two isomers, the study emphasizes on the development of pure enclomiphene isomer for treatment of hypogonadal men. 46 Edward D. Kim, Andrew McCullough and Jed Kaminetsky conducted a study to compare oral emclomiphene with topical testosterone gel and concluded that enclomiphene citrate consistently increased serum testosterone, lutienizing hormone and follicle stimulating hormone, restoring normal levels of serum testosterone and also maintained sperm concentrations in the normal range. Testosterone gel also restored total testosterone but sperm counts were not maintained.…”
Section: Studies On Enclomiphenementioning
confidence: 99%
“…Because of the different biochemical properties of the two isomers, the study emphasizes on the development of pure enclomiphene isomer for treatment of hypogonadal men. 46 Edward D. Kim, Andrew McCullough and Jed Kaminetsky conducted a study to compare oral emclomiphene with topical testosterone gel and concluded that enclomiphene citrate consistently increased serum testosterone, lutienizing hormone and follicle stimulating hormone, restoring normal levels of serum testosterone and also maintained sperm concentrations in the normal range. Testosterone gel also restored total testosterone but sperm counts were not maintained.…”
Section: Studies On Enclomiphenementioning
confidence: 99%